Pengaruh Quality Of Work Life, Internal Corporate Social Responsibility, Dan Work Life Balance Terhadap Employee Engagement Petugas Paramedis Rumah Sakit DKT Pagongan Tegal - Nafisa, Irma; Tyo, Gunis; Amalia, Mei Rani (Sains: Jurnal Manajemen dan Bisnis, 2024)
The test results in this research obtained: (1) Quality of Work Life has a partial effect on Employee Engagement which is shown by the calculated t value of 3.436 > t table 1.667 with a significant value of 0.001 < 0.05, (2) Internal Corporate Social Responsibility has a significant partial effect on Employee Engagement which is shown by the calculated t value of 3.045 > t table 1.667 with a significant value of 0.003 < 0.05, (3) Work Life Balance has a partial effect on Employee Engagement which is shown by the calculated t value of 10.207 > t table 1.667 with significant value 0.000 < 0.05, (4) Quality of Work Life, Internal Corporate Social Responsibility, and Work Life Balance simultaneously influence Employee Engagement as shown by the calculated F value 186.930 > F table 2.74 with a significant value 0.000 < 0.05. (5) Quality of Work Life, Internal Corporate Social Responsibility, and Work Life Balance have an influence on Employee Engagement by 51.9%, which is indicated by a coefficient of determination (R2) of 0.519.